2012
DOI: 10.1177/1748006x12459157
|View full text |Cite
|
Sign up to set email alerts
|

Skipping unnecessary structural airframe maintenance using an on-board structural health monitoring system

Abstract: Structural airframe maintenance is a subset of scheduled maintenance, and is performed at regular intervals to detect and repair cracks that would otherwise affect the safety of the airplane. It has been observed that only a fraction of airplanes undergo structural airframe maintenance at earlier scheduled maintenance times. But, intrusive inspection of all panels on the airplanes needs to be performed at the time of scheduled maintenance to ascertain the presence/absence of large cracks critical to the safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Pattabhiraman et al [4] showed that in its early life CBM can skip several scheduled maintenances because there is no considerable damage detected. In CBM, the maintenance time is determined by considering the detected damage size, the prognostics of damage growth, and the required level of reliability.…”
Section: Condition-based Maintenancementioning
confidence: 99%
“…Pattabhiraman et al [4] showed that in its early life CBM can skip several scheduled maintenances because there is no considerable damage detected. In CBM, the maintenance time is determined by considering the detected damage size, the prognostics of damage growth, and the required level of reliability.…”
Section: Condition-based Maintenancementioning
confidence: 99%
“…f N a ðÞ¼ha 0 ; fp ðÞ ; JC ; m ðÞ ðÞ (5) where a 0 ,f N a ðÞ , and fp ðÞrepresent the initial crack size, the probability density function of crack size after N cycles, and the pressure differential, respectively. JC ; m ðÞ is the joint probability density of the Paris-Erdogan model parameters C; m ðÞ .…”
Section: Direct Integration Proceduresmentioning
confidence: 99%
“…For a Boeing 737-300/400/ 500, the typical C check is carried out at about 2800 flight cycles (4000 flight hours with an average flight length of 1.4 h) [4]. This inspection schedule is chosen such that the probability of an undetected crack growing beyond the critical size before the next scheduled maintenance is less than 1 in 10 million [5].…”
Section: Introductionmentioning
confidence: 99%
“…7 Speckmann and Daniel 11 summarized the challenges and benefits of SHM for an airliner under in-service conditions and proposed a progressive introduction of SHM into the aeronautical industry. Pattabhiraman et al 12 developed a CBM-skip strategy to skip unnecessary scheduled structure maintenance using an on-board SHM system and argued that the strategy has the potential to lead to substantial cost saving over the traditional scheduled maintenance. Furthermore, a similar study was carried out by Cot et al 13 using a new probabilistic analytical mode instead of the Monte Carlo method used in Pattabhiraman et al 12 Fitzwater et al presented a cost/ benefit analysis of SHM on a specific damage-tolerant structure of F-15 fighter aircraft by integrating of SHM with traditional scheduled structure maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Pattabhiraman et al 12 developed a CBM-skip strategy to skip unnecessary scheduled structure maintenance using an on-board SHM system and argued that the strategy has the potential to lead to substantial cost saving over the traditional scheduled maintenance. Furthermore, a similar study was carried out by Cot et al 13 using a new probabilistic analytical mode instead of the Monte Carlo method used in Pattabhiraman et al 12 Fitzwater et al presented a cost/ benefit analysis of SHM on a specific damage-tolerant structure of F-15 fighter aircraft by integrating of SHM with traditional scheduled structure maintenance. The authors concluded it is unlikely that one-off conditional solutions are cost-effective and a systems approach encompassing many structural issues into a larger system might be more advantageous.…”
Section: Introductionmentioning
confidence: 99%